UPAYA KEPOLISIAN DALAM PENANGGULANGAN KEJAHATAN PERAMPASAN SEPEDA MOTOR DI JALAN RAYA (Studi Kasus di Polrestabes Semarang) - R. Sugiharto; Rina Lestari (UNISSULA, 2016)
Crime seizure of motorcycles that preceded violence to victims increasingly prevalent in Indonesia. This study aims to determine the factors causing the crime of motorbike seizure on the highway, knowing the efforts of the police in handling crime seizure of motorcycles on the road, knowing the constraints faced by the Police in tackling the seizure of motorcycles on the road and the solutions provided. The research method using sociological juridical approach with the object of study is criminal act of seizure of motor vehicle with violence. The results of the research are: 1) The factors that cause the motorcycle seizure is triggered by economic factors, the lack of employment, juvenile delinquency, and environmental factors, 2) the efforts made by the police in tackling the crime of motorcycle seizure among others Preventive and repressive efforts. 3) Obstacles faced by the police in tackling crimes of motorbike seizure on the highway include lack of information from the reporting party, the location of different events and the psychological condition of the victim that makes it difficult to dig deeper information and the solution for the community of motorcycle users to Do not travel at night in the area prone, do not try to drive alone, when feeling less comfortable atmosphere of honking continuously to attract attention of citizen, armed yourself.